Pelatihan Aplikasi Paket Niaga dan Internet di Cafetaria Tepi Kolam Kawasan Bukit Lawang Kabupaten Langkat, Sumatera Utara - Lestari, Yuyun Dwi; Muhammad Zen; Chairul Rizal; Barany Fachri (Jurnal Pengabdian Masyarakat, 2022)
Information technology has developed very rapidly and covers various fields. The field of education is one area that is influenced by information technology. Both in the formal learning process at school and non-formal in the form of training outside of school. The form of participation from universities in this community service activity is to provide skills training in the field of information technology through the application of commercial packages and the internet to the community of young people in the Afetaria Tepi Kolam Bukit Lawang, Kec. Bahorok, Kabupaten Langkat, Sumatera Utara of the Bukit Lawang Peduli Local Community through the Cahaya Anak Nusantara Foundation.